Ratio Decidendi Judge's Decision in Case Cancellation Marriage : Antinomy between Justice and Legal Certainty at the Cibinong Religious Court - Hakim, Uu Lukmanul; Sitorus, Charles Sugiarto; Mahipal, Mahipal; Asrun, Andi Muhammad; Wahyudin, Muhammad Nur Hussein (Politeknik Siber Cerdika Internasional, 2025)
Marriage annulment cases in Indonesia often reveal a fundamental tension between the principles of legal certainty and substantive justice, particularly in religious courts where statutory norms intersect with moral and cultural values. This study focuses on the annulment case Number 7584/Pdt.G/2021/PA.Cbn at the Cibinong Religious Court, where the judge’s decision prioritized a strict textual interpretation of the law, emphasizing legal certainty while potentially overlooking the moral and social harm experienced by the plaintiff. The purpose of this research is to analyze the ratio decidendi underlying the decision, examining how the balance between justice and legal certainty is operationalized in judicial practice. Using a juridical-normative approach, this study draws on statutory, conceptual, and case-based analyses supported by primary and secondary legal materials, including court decisions and relevant literature. The findings indicate that the court’s reasoning reflects a firm adherence to positive law, defining fraud narrowly in line with the Marriage Law and the Compilation of Islamic Law, and excluding failure to fulfill a dowry promise as a ground for annulment. While this ensures consistency, it limits judicial flexibility to address substantive justice. The implications of this study are twofold: first, it underscores the need for progressive interpretive methods, such as hermeneutic and teleological reasoning, to harmonize legal certainty with justice; second, it provides practical recommendations for judicial training, legislative reform, and scholarly frameworks that integrate maqasid al-shariah with positive law to guide future decisions.